(untitled) (Research, Society and Development, 2023)
The objective of this study is to characterize the nutritional status, biochemical profile and presence of comorbidities in women with gynecological and breast cancer. This is a cross-sectional and retrospective study, of quantitative nature, including women diagnosed with gynecological or breast cancer, followed up at the nutrition clinic. Data collection was performed through the application of a questionnaire that included sociodemographic, clinical, anthropometric and biochemical data. The prevalence ratios and the respective 95% confidence intervals were calculated by Pearson’s chi-square. Of the 108 eligible patients, most were overweight (66.67%) and low weight was identified in 12% of the women investigated. The mean BMI was 28.78±6.97 kg/m² and there was no significant difference according to the type of cancer (p=0.531). Low levels of hemoglobin were observed in 35.19% of the sample, 12.04% with microcytic and 16.67% with hypochromic anemia. The frequency of anemia was higher in gynecological malignancy (p=0.005) in addition to lower platelet values (p=0.045). The presence of comorbidities did not present significance in the comparison between cancers. Thus, it was identified in the studied sample that most women with female cancers were overweight. Hematimetric disorders were identified in greater proportions in patients with gynecological cancers.